If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + 9 = 55 Reorder the terms: 9 + H = 55 Solving 9 + H = 55 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + H = 55 + -9 Combine like terms: 9 + -9 = 0 0 + H = 55 + -9 H = 55 + -9 Combine like terms: 55 + -9 = 46 H = 46 Simplifying H = 46
| r-8.9=-8.3 | | 4(x-4)=-6(x+1)+46 | | d-9=11 | | -8x-(4yi)=12i+24 | | 8w+12=37.8 | | 24=n+13 | | X^2+y-49=0 | | 6x-12=30x | | 8-w=21 | | 2(x-1)+4x=-20 | | 0.7-0.36= | | -27n+6-2n+17=37+3n+3n | | 50+0.20=30+0.70 | | D=(r+c)t | | x=-2x+8 | | i+13=27 | | -1/1=4/8 | | 5(x-3)-x=1 | | 3x-10+2x=90 | | x^2-4x=a | | f(x)=x^2-5x-5 | | 15x+-6= | | 8p+56p=0 | | 10x^2+31x-63=0 | | 8x+2y=-7 | | 4+3n=40 | | 8x^2+2x+8=0 | | 0.5=y/8 | | -5/6y-7=18 | | dx/dt=sin2t | | 6x+3=11x | | 9x+5=7-(6x-9) |